2012
DOI: 10.1063/1.4704151
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-induced excess quasiparticles in superconducting resonators measured through correlated conductivity fluctuations

Abstract: We have measured the number of quasiparticles and their lifetime in aluminium superconducting microwave resonators. The number of excess quasiparticles below 160 mK decreases from 72 to 17 lm À3 with a 6 dB decrease of the microwave power. The quasiparticle lifetime increases accordingly from 1.4 to 3.5 ms. These properties of the superconductor were measured through the spectrum of correlated fluctuations in the quasiparticle system and condensate of the superconductor, which show up in the resonator amplitud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 26 publications
7
54
0
Order By: Relevance
“…Quasiparticle tunneling into a Cooper pair box has been used to detect far-infrared radiation from a blackbody source with a noise-equivalent power of less than 10 −19 W/Hz 1/2 , potentially providing a successor technology to kinetic inductance detectors [18]. In parallel, studies on superconducting resonators have shown a saturation of the quasiparticle population at a relatively high temperature of 140 mK [19]. It remains an experimental challenge to reduce the quasiparticle temperature towards the base lattice temperature in a dilution refrigerator.…”
mentioning
confidence: 99%
“…Quasiparticle tunneling into a Cooper pair box has been used to detect far-infrared radiation from a blackbody source with a noise-equivalent power of less than 10 −19 W/Hz 1/2 , potentially providing a successor technology to kinetic inductance detectors [18]. In parallel, studies on superconducting resonators have shown a saturation of the quasiparticle population at a relatively high temperature of 140 mK [19]. It remains an experimental challenge to reduce the quasiparticle temperature towards the base lattice temperature in a dilution refrigerator.…”
mentioning
confidence: 99%
“…The consequences of the redistribution of quasiparticles for the electrodynamic response were only studied theoretically for T > 0.5T c [10]. Redistribution of quasiparticles also explains [11] the microwave power dependent number of quasiparticles in microwave resonators at low temperatures, which we have recently measured [12]. These quasiparticles impose a limit for detectors for astrophysics based on microwave resonators [13,14].…”
mentioning
confidence: 99%
“…[12,29]. Figure 4(a) shows τ qp as determined from the cross-power spectral density of quasiparticle fluctuations in the amplitude and the phase of the resonator [12]. Panels (b) and (c) show the measured Q i and f res .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The lens-antenna coupled hybrid MKIDs have shown the expected photon noise limited performance in both phase and amplitude readout down to 100 fW of optical loading as well as a high optical efficiency 7,8 . A Noise Equivalent Power (NEP) in the 10 −19 W/ √ Hz range has been measured electrically for MKIDs 3,9 . The electrical NEP is determined from the MKIDs temperature responsivity, quasiparticle recombination time, superconducting energy gap and noise spectrum, all of which can be measured in a dark environment.…”
mentioning
confidence: 99%